Air and Soil Concentrations and Source Identification of Ambient Polychlorinated Biphenyls in the Northeastern Mediterranean Region. Issue 5 (28th March 2017) - Kuzu, Sadullah Levent; Saral, Arslan
Abstract : Ambient air and soil samples were taken in Istanbul between November 2012 and May 2013 in order to determine polychlorinated biphenyl (PCB) concentrations. A high volume air sampler was operated to collect air samples. Soil samples were taken from top of bare land. Air PCB concentrations ranged from 201 to 705 pg m −3 with an average of 360 pg m −3 . The dry weight soil PCB concentrations varied from 3.4 to 13.6 ng g −1 with an average of 8.3 ng g −1 . The fate of PCBs was investigated through gas/particle partitioning. Further investigation was made between soil and air phases by fugacity fractions. Effect of wind direction was revealed by conditional probability function (CPF). Potential source contribution function was employed to determine the likely distant PCB sources. Di‐chlorinated biphenyls (Di‐CBs) tended to accumulate in soil while 5‐, 7‐, and 8‐CBs volatilized from the soil. According to CPF, 3‐CBs were likely to be released from the Marmara Sea. Additionally, SW wind direction was dominant for Σ‐, 2‐, 5‐, 6‐, 7‐CBs, and concentration of 9‐CBs increased for the winds of NW, N, NE directions. Previously reported hot‐spot zones for iron‐steel manufacturing industry were identified to contribute to PCBs in air masses, arriving from SW direction. Additional contribution was detected when air masses arrived from the north. These sources were from the south of the Ukraine. Abstract : Polychlorinated biphenyls (PCBs) are ubiquitous persistent organic pollutants that can contaminate air from local or long‐range sources. Air and soil samples are collected and several models are applied to the data in order to identify the sources. Both local and long‐range sources contributes to PCBs levels. Fingerprint of iron‐steel manufacturing on PCB concentrations is identified.